Distribution of Natural Radionuclides in Songkhla Beach Sands - Prasong Kessaratikoon; Supphawut Benjakul; Suchin Udomsomporn (Agriculture and Natural Resources, 2007)
Specific activities and distribution of natural radionuclide γ-ray activities, produced by 40K, 226Ra and 232Th, were determined in 80 sand samples collected along the Chalatat and the Samila beaches in Songkhla province. The derivation of 40K, 226Ra and 232Th γ-ray specific activities of sand samples was performed by using the high-purity germanium (HPGe) detector and gamma spectroscopy analysis system and the Eu-152 radioactive standard source at the Office of Atoms for Peace (OAP) laboratory. The beach sand specific activity ranges from 89 – 963 Bq/kg for 40K, 0 – 120 Bq/kg for 226Ra and 0 – 319 Bq/kg for 232Th with mean values of 248 ± 44 Bq/kg, 41 ± 5 Bq/kg and 64 ± 7 Bq/kg, respectively. The specific activities of these radionuclides were compared with the OAP results and other global radioactivity measurements and evaluations. Moreover, gamma–absorbed dose rates and radium equivalent activities were calculated for the analyzed samples to assess the radiation hazards arising. All the beach sand samples had the mean value of radium equivalent activities lower than the limit set in the Organization for Economic Cooperation and Development (OECD) report.